Identifying ‘Sri Yeshu Khrishta Mahathmyam’, as evidence for coexistence of Hinduism and Christianity in India - Navaneethakrishnan, S.; Balakailasanathasarma, M. (University of jaffna, 2024)
Coexistence of diverse religious faith is found in many countries of the world. Christian Sanskrit Literature have a major role in religious Sanskrit Literature. Christians translated or Sanskritized their canonical works into Sanskrit in India. As a result, several Christian Sanskrit Literatures were originated in India. This study shed lights on one of the Christian Sanskrit Literature, namely Sri Yeshu Khrishta Mahathmyam (SYKM) which is the primary source book of this study. Objective of this study is to identify SYKM, as an evidence of peaceful coexistence Hinduism and Christianity in India. The study emphasized interpretations in the texts using Hermeneutic research method. Analysis of the study reveals that SYKM explains the glory of Jesus Christ with a brief account of his life and doctrines in Sanskrit. It has eight sections comprises Eight hundred and Fifty-Seven Sanskrit verses in Anushtub metre. The First section entitled Sri Maha Moktri Prathiksha explains the expectation of a great Redeemer in 112 verses. The Second section entitled Yesutpaththi Varnanam, is a narration of the birth of Jesus in 62 verses. Third section titled Adbhudakriya varnanam gives some accounts of the wonderful works and miracles of Jesus in 137 verses. Fourth chapter named Jegadgurupadesamala is a garland of instructions by the World’s Teacher, extending 285 Slokas. Fifth one titled Yesvah pranasamarpanam explains delivering up of the life by Jesus, and consists of 116 Slokes. Sixth named as Sriyesvah Swargarohanam describes ascension of Jesus into Heven in 70 verses. The Seventh section extending to 31 verses namely Khristiyamataparamarthikatvam is an argument to prove in opposition to the views of Hindus. Eighth section Prarthanapadhdhathih is a manual of prayer in 52 verses. In conclusion As the SYKM originated from the Hindu concept of Mahathmya it could be considered as an evidence of coexistence Hinduism and Christianity in India.
Keywords: Sanskrit literature; Christianity; Hinduism; Coexistence; Comparative religion